Adaptasi Sosial Akademik Mahasiswa Fakultas Ilmu Sosial Universitas Negeri Makassar - Ibrahim Ibrahim; Muh. Said; Muhammad Zulfadli (Seminar Nasional LP2M UNM, 2019)
This research is intended to analyze the academic social adaptation of the students of the Faculty of Social Sciences, Makassar State University. This research is a qualitative research. Phenomenological approach. Data collection using methods: interviews, observation, and documentation. Checking the validity of the data in this study include: Observation Persistence, Triangulation, Detailed Description, Auditing. The results showed that the form of academic social adaptation manifested in social adaptations before / before students whose form was through online-based access to information mainly from the official website of the institution, whatsapp application (WA Group), instagram and the like. As well as print and other electronic media. Pre-students from the beginning entered through PKKMB, reciprocal communicative interaction with Academic Advisers, "advocacy-doctrinization", activations of the Student WA Group. The quality of academic social adaptation forms shows systemic polarization in students' depths. In addition, the existing forms of social adaptation with their intensity and implications determine the color of acculturation of self-determination and the actualization of students' academic social. Urgen to study the concept of form and process in a culture of social adaptation that is smarter and applicable for the success of student studies on time. Keywords: adaptation, social academic, students